1997
DOI: 10.1038/ki.1997.32
|View full text |Cite
|
Sign up to set email alerts
|

IgG subclasses in patients with membranoproliferative glomerulonephritis, membranous nephropathy, and lupus nephritis

Abstract: Primary glomerulopathy can be classified into seven essential patterns based on histopathological studies. The pathogenesis of membranoproliferative glomerulonephritis (MPGN), and membranous nephropathy (MN), which show glomerular IgG deposition and induce mainly nephrotic syndrome, is not known. To clarify the role of IgG subclass in glomerulonephritis, we compared serum concentrations of IgG subclasses, the ratio of serum IgG subclasses to total IgG (%IgG subclass), and glomerular deposition of IgG subclasse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
118
2

Year Published

2001
2001
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(124 citation statements)
references
References 11 publications
4
118
2
Order By: Relevance
“…The nature of pathogenic antigen and antibodies in IMN remain yet elusive, and studies at the moment can only be focused on potentially relevant Ig subclasses. In this respect, IgG4 were found to concentrate in the glomerular deposits (25,26), while serum levels were selectively low for IgG2 (27). Identifying the specific antibodies and documenting their disappearance from the circulation after effective B cell inhibition would greatly enhance our understanding of the role of B cell-related mechanisms in IMN.…”
Section: Discussionmentioning
confidence: 99%
“…The nature of pathogenic antigen and antibodies in IMN remain yet elusive, and studies at the moment can only be focused on potentially relevant Ig subclasses. In this respect, IgG4 were found to concentrate in the glomerular deposits (25,26), while serum levels were selectively low for IgG2 (27). Identifying the specific antibodies and documenting their disappearance from the circulation after effective B cell inhibition would greatly enhance our understanding of the role of B cell-related mechanisms in IMN.…”
Section: Discussionmentioning
confidence: 99%
“…One might question the role of complement activation in human MN because the non-complement-fixing IgG4 isotype predominates in the immune deposits (29,53), and the C1qr 2 s 2 complex is quite large (M r ϳ 800 kDa), which undoubtedly impedes its access to the subepithelial space. Still, there is a good deal of circumstantial evidence that complement is activated in subepithelial immune deposits, including the presence of C3 and C5b-9 in many cases (48,99) and C3d in all cases of human MN (28); C3d is the stable C3 product generated from iC3b by factor I, presumably relying on podocyte CR1 as a cofactor.…”
Section: Implications For Human Mnmentioning
confidence: 99%
“…It is likely that specific types of human glomerulonephritis are associated with a polarization in the T cell response. For example, studies of human crescentic glomerulonephritis have shown that there is a predominant macrophage, T cell, and fibrin deposition that is consistent with a predominant Th1-type immune response (24,25), whereas in membranous nephropathy, there is IgG4 deposition within the glomerulus, an IgG subclass that is associated with a Th2 immune response (26).…”
mentioning
confidence: 99%